2016
DOI: 10.18632/oncotarget.7747
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-92b represses invasion-metastasis cascade of esophageal squamous cell carcinoma

Abstract: Invasion and metastasis are major contributors to cancer-caused death in patients suffered from esophageal squamous cell carcinoma (ESCC). To explore the microRNAs involved in regulating invasion-metastasis cascade of ESCC, we established two pairs of sublines (30-U/D and 180-U/D) with distinct motility capacity from two ESCC cell lines (KYSE30 and KYSE180). Screening of the differentially expressed microRNAs identified that microRNA-92b-3p (miR-92b) could dramatically inhibit invasion and metastasis of ESCC c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 43 publications
3
47
0
1
Order By: Relevance
“…Among these miRs, it has been observed that miR-92b serves a role in certain types of human cancer (17,18). miR-92b promotes the proliferation, migration and invasion of glioma cells, and induces apoptosis via regulation of the phosphatase and tensin homolog (PTEN)/protein kinase B signaling pathway (17).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these miRs, it has been observed that miR-92b serves a role in certain types of human cancer (17,18). miR-92b promotes the proliferation, migration and invasion of glioma cells, and induces apoptosis via regulation of the phosphatase and tensin homolog (PTEN)/protein kinase B signaling pathway (17).…”
Section: Introductionmentioning
confidence: 99%
“…miR-92b promotes the proliferation, migration and invasion of glioma cells, and induces apoptosis via regulation of the phosphatase and tensin homolog (PTEN)/protein kinase B signaling pathway (17). Additionally, miR-92b represses the invasion and metastasis of esophageal squamous cell carcinoma (ESCC) in vitro and in vivo , and higher expression of miR-92b in ESCC tissue is inversely correlated with lymph node metastasis and indicates better patient prognosis (18). Recently, it has been demonstrated that miR-92b promotes the malignant phenotype of osteosarcoma cells by inhibiting the expression of reversion-inducing, cysteine-rich protein with kazal motifs (RECK) (19).…”
Section: Introductionmentioning
confidence: 99%
“…Protein extraction and Western blotting were conducted as previously reported . The following antibodies were used in the present study: JNK (Catalog: A11119; ABclonal Technology); p‐JNK (Catalog: AP0808; ABclonal Technology); MEK5 (Catalog: A6953; ABclonal Technology); p‐ERK1/2 (Catalog: AP0472; ABclonal Technology); ERK1/2 (Catalog: D160317; Sangon Biotech); p‐38 (Catalog: D155224; Sangon Biotech); p‐p38 (Catalog: D155179; Sangon Biotech); ERK5 (Catalog: D120601; Sangon Biotech); β‐Actin (Catalog: AC026; ABclonal Technology).…”
Section: Methodsmentioning
confidence: 99%
“…The in-vitro invasion assay was performed in 24-well Boyden chambers (Corning Inc) pre-coated with the presence of Matrigel (BD Biosciences), as previously described. 33 Cells were counted from at least four randomly selected microscopic fields.…”
Section: Cell Invasion Assaymentioning
confidence: 99%
“…The involvement of miR-92b in tumor cell biology has been reported in many tumors including brain primary tumors, 25 neuroblastoma, 26 glioblastoma, 27 non-small cell lung cancer, 28 oral squamous cell carcinoma, 29 esophageal squamous cell carcinoma, 30 bladder cancer, 31 and colorectal carcinoma. 32 A previous study F I G U R E 4 Impact of hepatoma-derived exosomes and exosomal miR-92b on NK cell activity.…”
Section: Discussionmentioning
confidence: 99%